On the relationship between oil and equity markets: evidence from South Asia. Issue 3 (5th June 2017) - Noor, Md Hasib; Dutta, Anupam
Abstract : Purpose: The purpose of this paper is to investigate the volatility linkage between global oil market and major South Asian equity markets. Design/methodology/approach: In order to serve the purpose, the authors employ a recently developed vector autoregressive-generalized autoregressive conditional heteroskedastic model to examine whether shocks and volatility spill over from the oil market to various equity markets under consideration. Findings: The findings of the empirical analysis suggest that all the markets studied do receive volatility from the oil market. Not surprisingly, the authors do not find any significant evidence of volatility transmission from the equity markets to the global oil market. Additionally, while computing the optimal portfolio weights and hedge ratios, the authors document that inclusion of oil in the portfolio of stocks tends to reduce the risk of the resultant portfolio. Originality/value: Fully original.